MENTERI KESEHATAN SEBAGAI LEADING SECTOR DALAM PENANGANAN WABAH COVID-19 DITINJAU DARI TEORI KEWENANGAN - Defanny Fitri Anatasia (Gloria Justitia, 2021)
Based on the Government Regulation of the of Indonesia Number 21 of 2020, Large-Scale Social Restrictions (PSBB). The Ministry of Health is authorized to make technical regulations. Minister of Health made Minister of Health Regulation Number 9 of 2020, PSBB. Seems like the synergy between the Ministries hasn’t been implemented properly, ex. the Ministry of Law and Human Rights published Regulation of The Ministry of Law and Human Rights Number 10 of 2020 and The Ministry of Transportation with their Regulation Minister of Transportation Number 18 of 2020 changed to Regulation of Minister of Transportation 41 of 2020. The regulations contradict with the Minister of Health a quo regulation. Which regulation should be used? Who’s responsible for it? It’s necessary to review synchronization between Ministry regulations. This research used Normative Juridical, Literature Study, Interview, and Analysis Method. A brief conclusion if there’s a lawsuit against the a quo regulation then the responsibility lies with the Ministry of Health. Disharmonization between ministerial regulations can be resolved by Judicial Review, Mediation by the Ministry of Law and Human Rights, and applying the principles of Lex Superior Derogat Legi Inferiori, Lex Specialis Derogat Legi Generalis, and Lex Posterior Derogat Legi Priori Principles.